Methyl Jasmonate Cytotoxicity and Chemosensitization of T Cell Lymphoma In Vitro Is Facilitated by HK 2, HIF-1α, and Hsp70: Implication of Altered Regulation of Cell Survival, pH Homeostasis, Mitochondrial Functions - Goel, Yugal; Yadav, Saveg; Pandey, Shrish Kumar; Temre, Mithlesh Kumar; Singh, Vinay Kumar; Kumar, Ajay; Singh, Sukh Mahendra (Frontiers in Pharmacology, 2021)
Methyl jasmonate (MJ) displays antineoplastic potential against numerous neoplastic cells. However, several mechanistic aspects of its antineoplastic action against malignancies of T cell origin remain elusive. The present investigation reports the novel targets of MJ and mechanistic pathways of MJ-mediated antineoplastic and chemosensitizing action against tumor cells derived from murine T-cell lymphoma, designated as Dalton’s lymphoma (DL). The present study demonstrates that MJ directly docks to HIF-1α, hexokinase 2, and Hsp70 at prominent binding sites. MJ exhibits tumoricidal action against tumor cells via induction of apoptosis and necrosis through multiple pathways, including declined mitochondrial membrane potential, enhanced expression of ROS, altered pH homeostasis, an elevated level of cytosolic cytochrome c, and modulated expression of crucial cell survival and metabolism regulatory molecules. Additionally, this study also reports the chemosensitizing ability of MJ against T cell lymphoma accompanied by a declined expression of MDR1. This study sheds new light by demonstrating the implication of novel molecular mechanisms underlying the antitumor action of MJ against T-cell lymphoma and hence has immense translational significance.